Statistics and reality : concepts and measurements of migration in Europe - Fassmann, Heinz; Reeger, Ursula, 1965-; Sievers, Wiebke (IMISCOE reports., 2009)
"In the last decade, there has been a distinct trend towards a worldwide harmonisation of migration statistics, chiefly pushed by international bodies and organisations that need comparative data. Statistics and Reality shows that these attempts have as yet not been very successful. It provides an accessible account of the history of migration measurement in Europe and analyses the current conceptualisations of migration and data gathering procedures in twelve European countries in the context of their migration histories. Based on this analysis, the authors provide a critical insight into the migrant stocks and flows in their countries"--Publisher's description